ECG as a storytelling of cardiac involvement evolution in Anderson Fabry disease. (3rd October 2022) - Chiti, C; Ditaranto, R; Barlocco, F; Lillo, R; Re, F; Marchi, G; Parisi, V; Ferrara, V; Baldassarre, R; Di Nicola, F; Gimeno Blanes, J R; Graziani, F; et al.
Abstract: Background: Cardiac involvement in Anderson-Fabry disease (AFD) is related to a progressive glycosphingolipid storage over time and is characterized by left ventricular hypertrophy (LVH), conduction abnormalities and myocardial fibrosis. ECG is useful for early recognition of AFD, however evidence is limited on the association between ECG alterations and disease stage. Purpose: To assess the relationship between ECG characteristics and progressive cardiac involvement, from the pre-hypertrophic phase to phenotypes with increasing degree of LVH. Methods: In a multicenter cohort, 183 AFD patients (40% male, age 47±12 years, 60% affected by "classical AFD") underwent ECG and transthoracic echocardiography. Patients were divided into 4 groups according to the different degree of LV thickness measured in parasternal short axis view: group A ≤9 mm (N=46, 25%), group B 10–14 mm (N=77, 42%), group C 15–19 mm (N=45, 25%) and group D ≥20 mm (N=15, 8%). Patients with pacemaker and under 18 years of age were excluded. Results: A normal ECG was present in 89% in group A, 59% in group B, 11% in group C and it was absent in group D. Short PR (<120 ms) was more frequent in group A, whereas with LVH increasing, median PR interval duration significantly prolonged among the 4 groups (136 [125–150]vs 141 [130–160] vs 160 [130–180] vs 170 [130–180] ms, p=0.002 respectively). Median P-wave duration was shorter in group A and B compared to group C and D (80 m vs 100 ms, p<0.001), while both QRS and QTc gradually increased. Median Sokolow-Lyon voltage criteria statistically augmented among the groups (22 [18–26] vs 27 [20–33] vs 32 [25–45] vs 35 [18–40] mm, p<0.001 respectively), along with right ventricular hypertrophy (0%, 1%, 11%, 8%, p=0.02). Right bundle branch block (RBBB) had a higher frequency in advanced stages (0%, 34%, 34%, 40%, p<0.001), with a prevalence of complete RBBB of 46% in group D. Similarly, left anterior fascicular block (0%, 7%, 18%, 46%, p<0.001) and QRS fragmentation (2%, 11%, 25%, 23%, p=0.009) were more common in advanced stages. No differences were found in left bundle branch block (LBBB), in low QRS voltages or in LV pre-excitation prevalence. According with the wall thickness increase, negative T waves were more frequent in lateral (4%, 21%, 70%, 77%, p<0.001) and inferior leads (6%, 15%, 32%, 46%, p 0.001), as well as their association with ST-T depression (4%, 17%, 64%, 46%, p<0.001). Giant negative T waves were present only in group C and D (16% and 31%) mainly representing a LVH distribution toward the apex. Conclusions: ECG is a very useful tool to stage cardiac involvement evolution in AFD. Peculiar ECG characteristics evolve together with LV wall thickness: incomplete and progressively complete RBBB usually associated (preceding or following) LVH and/or typical repolarization abnormalities in inferior or lateral leads and giant negative T waves in the more advanced stages are the most frequent and typical ECG patterns. Funding Acknowledgement: Type of funding sources: None.